Adaptive time-varying output formation tracking control for multi-agent system with dynamic event-triggered strategies - Wu, Jie; Zhang, Xiaoyi; Zhan, Xisheng; Han, Tao; Yan, Huaicheng (Journal of computational science, 2025)
This paper investigates the output feedback time-varying formation(OFTVF) tracking issue for general linear multi-agent systems(MASs). To address this issue, novel dynamic event-triggered(DET) strategies are proposed to manage the inter-agent communication effectively. It removes the assumption that constant interaction is required between agents, and therefore communication cost is reduced significantly. Then under the proposed DET strategies, an adaptive OFTVF tracking control algorithms is designed for general linear MASs. Using Lyapunov stability theory, it is demonstrated that under proper conditions the proposed protocol is implementable. Furthermore, for the constructed DET scheme, no agent exhibit the Zeno behavior. Simulation example is presented at the end of the paper to demonstrate the effectiveness of designed DET control mechanism.